STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENUMBUHKAN SIKAP TOLERANSI SISWA (Studi Kasus di SMA A. Wahid Hasyim) - Rahma Mahendra; Ali Said (JURNAL ILMIAH NUSANTARA, 2024)
At school, we are always taught about tolerance among others, which is all contained in the Pancasila, namely Bhineka Tunggal Ika, which means different but still one, and not infrequently we are also taught about helping and respecting each other regardless of anything and anyone, regardless of ethnicity, race, language, and religion. Therefore, schools have an important role in instilling an attitude of tolerance.In an institution, religious education is very necessary. This is because religious education has a very big influence on a life and through religious education that indirectly the attitude of tolerance will be formed slowly.The objectives of this study include: 1. To find out the PAI teacher's strategy in fostering students' tolerance attitude at SMA A. Wahid Hasyim. 2. To find out the impact of the implementation of PAI teachers' strategies in fostering students' tolerance attitude at SMA A. Wahid Hasyim. 3. To find out the supporting and inhibiting factors of PAI teachers in fostering students' tolerance attitude at SMA A. Wahid Hasyim.This research was conducted at SMA A. Wahid Hasyim Tebuireng Jombang. By using a case study approach which aims to find out something in depth. This research is included in qualitative field research by analyzing several things related to learning fiqh with an environmental perspective in the scope of a Madrasah. The data obtained are the results of observations, interviews and documentation which are then analyzed and conclusions are drawn.Based on this research, it is found that the results of the Islamic religion teacher's strategy in fostering the attitude of tolerance of students are very good. Most students already understand and apply the attitude of tolerance. It's just that, there are a small number of students who have not been able to apply the attitude of tolerance, maybe it's the influence of the student's environment in his daily life. However, the Islamic religion teacher will continue to try so that students who have not been able to apply the attitude of tolerance can understand or apply the attitude of tolerance both at school and outside school.